The role of Helicobacter pylori in minimal hepatic encephalopathy - Seham S El-seid; Fatma A Attia; Mona Abd El-Raouf; Ghada S Abd Al-Azeem; Nagwa Abd EL-Ghaffar Mohammed; Heba Anwar (SpringerOpen, 2015)
Background One of the causes of death in patients with liver cirrhosis is hepatic encephalopathy (HE). Hyperammonemia is the most important cause of HE. Aim The aim of this work was to determine the relation between the Helicobacter pylori infection and minimal hepatic encephalopathy (MHE) in cirrhotic patients and to assess the outcome after treatment of H. pylori. Patients and methods This study was carried out on 50 Egyptian cirrhotic patients. The patients were divided into two groups: group A1 (32 positive H. pylori) and group A2 (18 negative H. pylori). Both groups were compared with 20 (age and sex matched) healthy individuals (group B). Patients and controls were subjected to an assessment of history, clinical examination, upper gastrointestinal endoscopy with gastric biopsy for histopathological examination of H. pylori, abdominal ultrasound, neuropsychiatric assessment using the figure connection test (FCT), complete blood count, liver and kidney function tests, and determination of plasma ammonia level. Plasma ammonia level and FCT were measured before and after treatment of H. pylori among patients with positive H. pylori. Results Plasma ammonia levels and FCT were highly significantly increased in all cirrhotic patients (group A) compared with the controls (group B) (P < 0.01) and in the positive H. pylori patients (group A1) compared with the negative H. pylori patients (group A2) (P < 0.01) and in group A1 before treatment compared with after treatment (P < 0.01). Conclusion s There is a highly significant association between H. pylori infection and MHE in cirrhotic patients. The treatment of H. pylori infection reduces the mean plasma ammonia levels and improves FCT Results among the infected patients. Therefore, H. pylori infection is an effective treatable risk factor for the clinical management of MHE.